Retroperitoneal kaposiform hemangioendothelioma with kasabach-merritt phenomenon in children: A case report and review of the literature - Huo, Junming; Chen, Song; Li, Jing; Liu, Chengjun (Frontiers in Pediatrics, 2023)
Objective: To investigate the clinical features, diagnosis and treatment methods and prognosis of retroperitoneal Kaposiform hemangioendothelioma (R-KHE) in children. Methods: The clinical data of an infant with R-KHE was retrospectively analyzed. Literature on R-KHE in pediatrics were retrieved in databases including Wanfang, CNKI and PubMed as of April 2022. Results: A 1 month and 6 days female infant with R-KHE was reported. After the diagnosis was confirmed by biopsy and pathological examination, the patient was treated by interventional embolization, and a combined therapy with glucocorticoid, vincristine, sirolimus and propranolol. The patient has been followed up for 1 year and 2 months, and is still alive with tumor. Through literature search, a total of 15 children, together with the case in our report, were included. The main manifestations were diversity among those patients. 14 cases have combined Kasabach-Merritt phenomenon (KMP). 6 cases accepted surgery plus drug therapy. 4 cases accepted only surgery, and 4 cases only accepted drug therapy. While drug therapy plus radiotherapy were employed to 1 case. Improvement was observed in 11 cases, with significantly reduced tumor and survival with tumor. Tumor disappeared completely in 2 cases. While 2 cases suffered death. Conclusion: R-KHE has diverse clinical presentations and non-specificity in symptoms and imaging examinations, and most cases accompanied with KMP. Methods for R-KHE treatment include surgical resection, interventional embolization and drug therapy. Close attention needs to be paid to the adverse reactions of the drug during the course of treatment.